The effect of cement modification on the rheological properties of cement paste - Janavičius, Eugenijus; Daukšys, Mindaugas; Skripkiūnas, Gintautas; Nagrockienė, Džigita; Daugėlienė, Ala (Journal of Civil Engineering and Management, 2014)
Experimental tests have determined the effect of slag, opoka (silica-calcite sedimentary rock), silica fume (SiO2) suspension, dolomite dust and sodium silicate solution (NaSS) together with the polycarboxylatether based plasticizing admixture on the yield stress and viscosity of Portland cement paste the rheological properties of which have been defined applying a rotational viscometer with co-axial cylinders. The tests have revealed that slag, opoka, silica fume suspension and dolomite dust added to cement paste by replacing 10% of Portland cement (by weight) have an effect on the yield stress and viscosity of the paste subject to the form and fineness of additive particles. When 10wt% of Portland cement is replaced with slag cement, the yield stress of Portland cement paste reduces by about 25.9%, and viscosity increases by about 3.5 times compared with the yield stress and viscosity of reference cement paste. The yield stress of Portland cement paste with 0.5% NaSS admixture increases insignificantly, and viscosity grows approximately twice compared with reference cement paste. The tests have also showed that the modifying admixtures of Portland cement paste enable to control the rheological properties of cement paste.